A method to incorporate interstitial components into the TPS gynecologic rigid applicator library - Otal, Antonio; Richart, Jose; Rodriguez, Silvia; Santos, Manuel; Perez-Calatayud, Jose (Journal of Contemporary Brachytherapy, 2017)
Purpose: T2 magnetic resonance imaging (MRI) is recommended as the imaging modality for image-guided brachytherapy. In locally advanced cervical carcinoma, combined endocavitary and interstitial applicators are appropriate (Vienna or Utrecht). To cover extensive disease, Template Benidorm (TB) was developed. Treatment planning system applicator libraries are currently unavailable for the Utrecht applicator or the TB. The purpose of this work is to develop an applicator library for both applicators. Material and methods: The library developed in this work has been used in the Oncentra Brachytherapy TPS, version 4.3.0, which has a brachytherapy module that includes a library of rigid applicators. To add the needles of the Utrecht applicator and to model the TB, we used FreeCAD and MeshLab. The reconstruction process was based on the points that the rigid section and the interstitial part have in common. This, together with the free length, allowed us to ascertain the position of the tip. Results: In case of the Utrecht applicator, one of the sources of uncertainty in the reconstruction was determining the distance of the tip of needle from the ovoid. In case of the TB, the large number of needles involved made their identification time consuming. The developed library resolved both issues. Conclusions : The developed library for the Utrecht and TB is feasible and efficient improving accuracy. It allows all the required treatment planning to proceed using just a T2 MRI sequence. The additional use of specific free available software applications makes it possible to add this information to the already existing library of the Oncentra Brachytherapy TPS. Specific details not included on this manuscript will be available under request. This library is also currently being implemented also into the Sagiplan v 2.0 TPS.